Allorecognition of HLA-C Mismatches by CD8+ T Cells in Hematopoietic Stem Cell Transplantation Is a Complex Interplay between Mismatched Peptide-Binding Region Residues, HLA-C Expression, and HLA-DPB1 Disparities - Bettens, Florence; Buhler, Stéphane; Tiercy, Jean-Marie (Frontiers in Immunology, 2016)
HLA-C locus mismatches are the most frequent class I disparities in unrelated hematopoietic stem cell transplantation (HSCT) and have a detrimental impact on clinical outcome. Recently, a few retrospective clinical studies have reported some variability in the immunogenicity of HLA-C incompatibilities. To get better insight into presumably permissive HLA-C mismatches we have developed a one-way in vitro mixed lymphocyte reaction (MLR) assay allowing to quantify activated CD56-CD137+CD8+ lymphocytes in HLA-C incompatible combinations. T cell-mediated alloresponses were correlated with genetic markers such as HLA-C mRNA expression and the number of amino acid mismatches in the α1/α2 domains (peptide binding region). Because of the high rate of HLA-DPB1 incompatibilities in HLA-A, B, C, DRB1 and DQB1 matched unrelated HSCT patient/donor pairs, the impact of HLA-DPB1 mismatching, a potential bystander of CD4+ T cell activation, was also considered. Heterogeneous alloresponses were measured in 63 HLA-C mismatched pairs with a positive assay in 52% of the combinations (2.3-18.6% activated CTLs), representing 24 different HLA-A~B~DRB1~DQB1 haplotypes. There was no correlation between measured alloresponses and mRNA expression of the mismatched HLA-C alleles. The HLA-C*03:03/03:04 mismatch did not induce any positive alloresponse in 5 MLRs. We also identified HLA-C*02:02 and HLA-C*06:02 as mismatched alleles with lower immunogenicity, and HLA-C*14:02 as a more immunogenic mismatch. A difference of at least 10 amino acid residues known to impact peptide/TCR binding and a bystander HLA-DPB1 incompatibility had a significant impact on CTL alloreactivity (p=0.021). The same HLA-C mismatch, when recognized by two different responders with the same HLA haplotypes, was recognized differently, emphasizing the role of the T-cell repertoire of responding cells. In conclusion, mismatched HLA-C alleles differing by10 or more amino acids in the peptide/TCR binding region, when occurring together with HLA-DPB1 incompatibilities, should be considered as high risk mismatches in unrelated HSCT.